Pengaruh Disiplin Kerja dan Fasilitas Kerja Terhadap Produktivitas Kerja Karyawan pada PT Sinar Sosro Cabang Bekasi - Ryan Dwi Pangga; Ana Ramdhayanti; Usran Masahere (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to explain the effect partially and simultaneously between the variables of work discipline and work facilities on employee productivity. This type of research uses quantitative research because it leads to measurement methods and samples to test variables and hypotheses. By using the SPSS version 27 program, researchers conducted several tests including validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, t tests, F tests, multiple linear regression analysis and test the coefficient of determination, the results of this study indicate that the regression equation the value of the effect of work discipline = 0.400 and the value of work facilities = 0.77 so that it has a positive influence on employee work productivity. multiple linear regression analysis and coefficient of determination tests. The population in this study totaled all employees of Employee Work Productivity at PT Sinar Sosro (Bekasi branch), and the number of samples in this study were 40 people. The results of this study show that work discipline has a partial and significant effect on employee productivity. Work facilities have a partial and significant effect on employee productivity. Work Discipline and Work Facilities simultaneously influence employee productivity.